MAKNA PUISI âAS-SÄªRATU AÅ»-Å»ÄTIYYATU LI SAYYÄFIN âARABIYYINâ DALAM ANTOLOGI PUISI AL-QAá¹¢ÄâIDU ASSIYÄSIYYATU KARYA NIZÄR QABBÄNIY: ANALISIS SEMIOTIK RIFFATERRE - , IMAN FIRMANSYAH, Dra. Hindun, M.Hum ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Poetry is kind of literature that has meaning of meaning. In order to understand it, poetry should researched by theory of semiotic. Semiotic is a research model which takes note of the symbols. These symbols was found from the language which used in the literatureâs work. This thesis is a result of research about explaining poetryâs meaning of meaning which used Riffaterreâs semiotic theory. The data that used in this research is a poetry under the title as-SÄ«ratu aÅ¼-Å»Ätiyyatu li SayyÄfin âArabiyyin, which is written by Syrian poet, NizÄr QabbÄniy. This poetry talks about the dictator and tyrannical Arabian king. The king of this poetry is feeling that he was a strong man, a powerfull man, a great man, has the authority, and has the good looking. But the king of this poetry is always does the cruels to his peoples, he is so ruling and he is saying that himself is god and other is so very weak. Beside it, this poetry talks about the life style of the king which is full of the luxurious and the happiness. Itâs so different with the life style of his peoples which is full of the suffering. The dictator and tyrannical Arabian king in this poetry is a Nizarâs critic to all the kings of Arabic countries.